Financial Stability – Comparative Analysis: Montenegro, Serbia and the Netherlands - Milena Vučinić (Journal of Central Banking Theory and Practice, 2015)
The global financial crisis has had far-reaching effects on financial systems and economies all over the world, thus putting the importance of safeguarding financial stability in the focus of interest of the global economy. This paper presents the importance of safeguarding financial stability and building a strong financial system with developed early identification and successful management of risks, i.e. a system resilient to shocks and capable of overcoming them. The paper focus is on the issue of financial stability of Montenegro, given through comparative analysis of the financial stability safeguarding frameworks in the Netherlands and the Republic of Serbia. The paper aims to present the regulatory institutional framework for safeguarding financial stability, and the measures that the countries take in order to achieve stability of their macroeconomic environment and financial system. The comparison of the characteristics and the approach to safeguarding the banking sector is particularly emphasised due to its major influence on the financial system stability.
Keywords: E52; E58; E62; 330; financial system; financial (in)stability; macroeconomic stability; fiscal consolidation measures; risk management